Digital Competencies in Escuela de Cadetes General Santander [ECSAN] cadets for the improvement of police service planning in coexistence and citizen security - Ospina, Daniela (2024)
Digital competencies are necessary in a technologically advancing context, as they become an opportunity to optimize the planning methods of the police service. The objective of this article was to determine the digital competencies of the cadets at the General Santander Cadet School [ECSAN], focusing on the planning of police service in coexistence and citizen security. To achieve this, a sequential explanatory mixed-methods approach was implemented, developed through the application of two instruments: a Likert-type survey administered to 157 students and a semi-structured interview conducted with eight teaching experts. Additionally, the academic curriculum and the study plan of the Master's in Coexistence and Citizen Security, as well as the specialization in Police Administration, were analyzed. Regarding the results, it was found that planning and systematization competencies tend to score higher compared to data analysis competencies. This indicates a need to strengthen this skill. While the results were optimal (with a percentage above 65%) in all competencies, it is also true that we are in a rapidly advancing digital era. Therefore, proposing improvements in these competencies could strengthen the planning of the police service in coexistence and citizen security. Hence, it is proposed to implement a pedagogical approach based on the extended classroom to provide experiences that grant training in the digital competencies identified here.